2013
DOI: 10.1142/s0217751x1350139x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noncommutativity on Light Hydrogen-Like Atoms and Proton Radius

Abstract: We study the corrections induced by the theory of non-commutativity, in both space-space and space-time versions, on the spectrum of hydrogenlike atoms. For this, we use the relativistic theory of two-particle systems to take into account the effects of the reduced mass, and we use perturbation methods to study the effects of non-commutativity.We apply our study to the muon hydrogen with the aim to solve the puzzle of proton radius [R. Pohl et al., Nature 466, 213 (2010) and A. Antognini et al., Science 339, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Equation (9) for θ 0i = 0 and θ i j = 0, has been already considered to find bound on the NC-parameter in hydrogen atom [71,[73][74][75]. The temporal part of the non-commutativity leads to a problem with the unitarity.…”
Section: Hydrogen Atom In Non-commutative Space-timementioning
confidence: 99%
See 1 more Smart Citation
“…Equation (9) for θ 0i = 0 and θ i j = 0, has been already considered to find bound on the NC-parameter in hydrogen atom [71,[73][74][75]. The temporal part of the non-commutativity leads to a problem with the unitarity.…”
Section: Hydrogen Atom In Non-commutative Space-timementioning
confidence: 99%
“…Here we would like to study the two-body bound state in non-commutative space to explore the differences in the electronic and muonic hydrogen spectrum. There are many studies on the hydrogen atom in the NC space-time [70][71][72][73][74][75][76][77][78][79][80]. However, the effect of NC space on the hydrogen atom at the lowest order is doubtful.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 15 years, there has been an increasing interest to study noncommutative standard model as a candidate for beyond Glashaw, Weinberg and Salam model of particle physics [1][2][3][4][5][6][7][8]. This is partially because of the modern foundations of string theory, where in its context it was shown that noncommutative models occur in description of low energy excitations of open strings in the presence of a constant background B-field [9].…”
Section: Introductionmentioning
confidence: 99%